Micro-Dynamics of Industrial Competition: Evidence from Korean Manufacturing Plants - Sung Wook Joh (Korea Development Institute (KDI), 2000)
This article examines the dynamic industrial competitive process in Korea through an analysis of determinants and consequences of industry turnovers. Entering firms include both entirely new producers (births) and producers that have moved in from another industry (switch-ins). Likewise, exiting producers include both producers that close their businesses (deaths) and producers that move into another industry (switch-outs). Using data of 690,000 establishments from 580 industries between 1990 and 1998, this paper shows that the turnover rate in Korea is one of the highest among countries. Statistical analysis shows that a large part of turnover variance is related to industry specific factors. At the same time, the analysis shows that macro-effects (GNP growth and inflation) industry characteristics (industry growth rate, capital requirement, market concentration, etc.) and producer specific factors (efficiency) affect industry turnover rates and performance at the plant level differently. The study also shows continual replacement of inefficient producers by efficient producers. In addition, the study also finds that the performance of entrants and dying plants was lower than that of continuing plants. Moreover, birth plants show better performance than dying plants. The paper also shows that the performance of surviving entrants has improved while that of dying plants has deteriorated over time. Such observation provides an important implication. Because entrants use resources released from closing plants and their performance improves over time, turnovers will improve efficient resource allocation.
Keywords: 330